Planning and the rural environment - Davidson, Joan.; Wibberley, G. P. (Oxford ; New York : Pergamon Press, 1977)
This book is about the changing fabric of the open countryside: a field neglected by planners who have been preoccupied with the built in environment of both town and country
Includes bibliographical references and index.
ijb, 17/01/2019
Loans
Keywords: Regional planning; Land use, Rural